0262 Associations Between Sleep And Mental Health In Children Aged 9 And 10 Years. (12th April 2019) - Goldstone, Aimee; Claudatos, Stephanie A; Lim, Yun Qi; Smith, Ellen; Gil, Maureen; Alschuler, Vanessa R; Rosas, Leonardo D; Prouty, Devin E; Clark, Duncan B; Hasler, Brant P; Franzen, Peter L; Zambotti, Massimiliano de; et al.
Abstract: Introduction: As children approach adolescence, they are at increased risk for mental health disorders, particularly girls. Sleep disturbances may contribute to this increased risk. Here, we investigated associations between sleep and mental health in a nationally-representative sample of 4521 US children (2146 female, aged 9-10 years) in the Adolescent Brain Cognitive Development (ABCD) study. Methods: Measures of child sleep disturbance (Disorders of Initiating and Maintaining Sleep (DIMS), Disorders of Arousal (DA), Sleep-Wake transition Disorders (SWTD) and Disorders of Excessive Somnolence (DOES)) and 'typical' total sleep time (TST) (i.e. number of hours slept on most nights in the past six months) were obtained from the parent-report Sleep Disturbance Scale (Data Release 1.1). Parent-report measures of child mental health (anxiety, depression, internalizing and externalizing behaviors, stress) from the Child Behavior Checklist and number of hours spent using media devices (screen-time) and pubertal development scale (PDS) were also included. Results: After controlling for PDS, parent education level, race, sex and ethnicity, DIMS and DOES were most associated with depression symptoms (β=0.51 & β=0.45) and weekday screen-time (β=0.09 & β=0.04). SWTD were most associated with anxiety symptoms (β=0.35) and DA were most associated with internalizing behaviors (β=0.25). Models accounted for 7-28% of the variance in each case. Compared to white participants, black participants experienced greater DIMS and SWTD and shorter TST. Lower parental education attainment was also associated with shorter TST while longer TST was identified for Hispanic, compared to non-Hispanic participants, and for girls compared to boys. Finally, more advanced PDS was associated with greater DOES, DA and SWTD and shorter TST. Conclusion: Here we identified significant demographic differences in TST and associations between mental health symptoms and sleep disturbances in a large sample of 9-10 year olds. Future longitudinal analysis of data from the ABCD study, the largest ever, longitudinal study about adolescent development, will allow investigation of how TST and sleep quality may mediate or predict the onset of mental health disorders during adolescence. Support (If Any): NIH 5U01DA041022-04 (SRI) U01DA041028 (Pittsburgh)